Acoustic and piezoelectric properties of 0-3 barium zirconate titanate-portland cement composites-effects of BZT content and particle size - Ruamporn Potong (2018)
Lead-free 0-3 Barium zirconate titanate (BZT)-Portland cement (PC) composites, environmentally friendly piezoelectric materials, which are expected to find applications in smart concrete structures due to their good compatibility with the host concrete, are studied. The results indicate that the composites can be tuned to a compatible value to match the requirement of concrete structure. For 425 μm BZT particle size used for the range tested at the same volume led to optimum piezoelectricity in composites. The electromechanical coupling coefficient was found to be ≈17% for 70% BZT composite. Several mathematical models are applied for the calculation of the piezoelectric coefficient of the composites and the experimental results were closest to those calculated from the cube model. © 2013 Copyright Taylor and Francis Group, LLC.